The effects of cocaine exposure in adolescence: Behavioural effects and neuroplastic mechanisms in experimental models. (8th June 2021) - Caffino, Lucia; Mottarlini, Francesca; Zita, Gianmaria; Gawliński, Dawid; Gawlińska, Kinga; Wydra, Karolina; Przegaliński, Edmund; Fumagalli, Fabio
Abstract : Drug addiction is a devastating disorder with a huge economic and social burden for modern society. Although an individual may slip into drug abuse throughout his/her life, adolescents are at higher risk, but, so far, only a few studies have attempted to elucidate the underlying cellular and molecular bases of such vulnerability. Indeed, preclinical evidence indicates that psychostimulants and adolescence interact and contribute to promoting a dysfunctional brain. In this review, we have focused our attention primarily on changes in neuroplasticity brought about by cocaine, taking into account that there is much less evidence from exposure to cocaine in adolescence, compared with that from adults. This review clearly shows that exposure to cocaine during adolescence, acute or chronic, as well as contingent or non‐contingent, confers a vulnerable endophenotype, primarily, by causing changes in neuroplasticity. Given the close relationship between drug abuse and psychiatric disorders, we also discuss the translational implications providing an interpretative framework for clinical studies involving addictive as well as affective or psychotic behaviours. LINKED ARTICLES: This article is part of a themed issue on New discoveries and perspectives in mental and pain disorders. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.17/issuetoc